Target Training to the Goal on Shooting Accuracy in Futsal for High School Students - Asdar Musa; Muhammad Sahib Saleh; Fahrizal Fahrizal (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This research is motivated by the importance of shooting accuracy as a crucial skill in futsal, which is often not optimally achieved by school-level athletes. The primary objective of this study was to evaluate the effectiveness of the target training model in improving the shooting accuracy of extracurricular futsal athletes at High School 5 Barru. Using a quasi-experimental method with a two-group pretest-posttest design, a sample of 22 players was selected through purposive sampling and divided into experimental and control groups. Data were collected through shooting accuracy tests and analyzed using descriptive and inferential statistics. The findings showed a significant improvement in the experimental group, with the average score increasing from 11.55 during the pretest to 17.91 in the posttest, representing an increase of 55.1%. Statistical analysis via paired sample t-test yielded a calculated t-value of 5.670, which exceeds the t-table value of 2.086 (df=20; alpha=0.05) with a significance value of 0.000 < 0.05, confirming that the working hypothesis is convincingly accepted. In contrast, the control group showed no significant change, with a calculated t-value of only 0.319 and a significant level of 0.756 > 0.05. These findings provide empirical evidence that the target training model is a valid and effective method for optimizing athletes' shooting techniques systematically and measurably compared to conventional training.